2013
DOI: 10.1108/scm-05-2013-0149
|View full text |Cite
|
Sign up to set email alerts
|

Supply and demand chain management: the effect of adding services to product offerings

Abstract: Purpose -The purpose of this paper is to understand how firms manage their product and service offerings, integrating supply chain management (SCM) and demand chain management (DCM) strategies. Adding services to the product portfolio of a firm may bring benefits to an organisation, but requires a reconsideration of the supply chain management approach. Design/methodology/approach -A survey is used to collect data, with valid questionnaires obtained for 4,227 UK-based respondents. Empirical analysis utilises s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 79 publications
(142 reference statements)
2
88
1
4
Order By: Relevance
“…The transit from traditional product-based firms to service orientation is complex and contextual. Bustinza, Parry, and Vendrell-Herrero (2013) proposed that this requires a reconsideration of the management of supply and demand chains. Vendrell-Herrero et al (2017) explored how servitisation affect upstream-downstream firms interdependencies in the context of digital business models, and found that digital services could empower upstream and downstream firms differently under certain circumstances.…”
Section: Product-service Systemsmentioning
confidence: 99%
“…The transit from traditional product-based firms to service orientation is complex and contextual. Bustinza, Parry, and Vendrell-Herrero (2013) proposed that this requires a reconsideration of the management of supply and demand chains. Vendrell-Herrero et al (2017) explored how servitisation affect upstream-downstream firms interdependencies in the context of digital business models, and found that digital services could empower upstream and downstream firms differently under certain circumstances.…”
Section: Product-service Systemsmentioning
confidence: 99%
“…The conclusions agree with DeSarbo et al [DeSarbo et al, 2001] and provide empirical evidence of the importance of consumer value analysis when firms deal with heterogeneous markets. This paper also contributes to the understanding that product and services need to be managed in different ways [Bustinza et al, 2013a]. Services are more amenable to global upstream delivery, whereas product format relies upon national or regional assets [Graham et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…This proposal leads to the formulation of the following set of hypotheses: Hypothesis 1. Ngo, 2011;Vargo, Lusch, 2004] such that it is possible, using the appropriate mix of value offerings [Ngo, O'Cass, 2009], to engage with and influence consumers and increase their likelihood of making a purchase [Bustinza et al, 2013a]. According to this argument, and considering the particular characteristics of potential music consumers, it is expected that specific value strategies can positively influence consumer attitudes.…”
Section: Context and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations